Competitiveness and cohesion: urban government and governances strains of Italian cities - Governa,Francesca (2010)
This article discusses current limitations and opportunities in Italian urban governance. Since the 1990s Italy has been going through changes concerning its political and institutional system. The changes in the roles and organisation of the State and more generally for the public actors, recognisably affects urban governments. Italian urban policies are therefore called upon to deal with the introduction of inter-institutional forms of cooperation between various levels of government; co-ordination between a multiplicity of actors and interests; involvement of private sector institutions; and the direct participation of citizens in the decision making processes. Much less clear is whether and how the debate around the different dimensions of urban governance has gained real influence - including in the governance practices of cities and in the capacity of policies to address urban problems.